2017
DOI: 10.1002/ajhb.23056
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal patterns in BMI and percent total body fat from peak height velocity through emerging adulthood into young adulthood

Abstract: Objectives: Emerging adulthood, a potential critical period, is an understudied period of fat mass accrual. The aim of this study was to describe patterns of fat mass accrual, and weight status, from adolescence, through emerging adulthood, into young adulthood.Methods: One-hundred-eighteen participants (59 male) were measured repeatedly for 20 years. Annual measures of height, weight, and body composition (DXA) were taken. Calculated measures included: peak height velocity (PHV), biological age (BA; years fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
(71 reference statements)
3
13
0
Order By: Relevance
“…Longitudinal data was used but not all participants were included in every measure, although the models did adjust for such missing data. With that said, the direction of the differences, by both sex and metric, have been demonstrated previously and a similar age at onset of overweight status identified (Wisemandle et al, 2000;E. Barbour-Tuck, Erlandson, Muhajarine, Foulds and A. D. G. Baxter-Jones, 2018).…”
Section: Limitationssupporting
confidence: 70%
See 1 more Smart Citation
“…Longitudinal data was used but not all participants were included in every measure, although the models did adjust for such missing data. With that said, the direction of the differences, by both sex and metric, have been demonstrated previously and a similar age at onset of overweight status identified (Wisemandle et al, 2000;E. Barbour-Tuck, Erlandson, Muhajarine, Foulds and A. D. G. Baxter-Jones, 2018).…”
Section: Limitationssupporting
confidence: 70%
“…Although it is known that normal weight youth become overweight adults during emerging adulthood (Wisemandle et al, 2000) the exact timing during emerging adulthood has not been identified and neither have sex differences by overweight status metrics (Wisemandle et al, 2000;E. Barbour-Tuck, Erlandson, Muhajarine, Foulds and A. D. G. Baxter-Jones, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Trunk fat mass, and particularly visceral fat, is not typically accrued until or shortly after the onset of puberty , but secular trends of increasing trunk fat mass (and/or visceral fat) may be conferring earlier risk in children. This is likely why our current findings suggest that trunk fat mass measured as young as 8 years of age can identify elevated future cardiometabolic risk scores despite only 14% of participants having been identified as having overweight or obesity by BMI cutoffs in adolescents .…”
Section: Discussionmentioning
confidence: 74%
“…Statistics Canada reports an almost twofold increase in rates of OWO from adolescents (12‐17 years; 23%) to young adulthood (20‐35 years; 42%) . In the Saskatchewan Pediatric Bone Mineral Accrual Study (PBMAS), we found that at peak height velocity (PHV) (11‐14 years of age), 9% of males and 14% of females had OWO, rising to 65% and 32%, respectively, 15 years after PHV years of age) . This underscores the importance of identifying contributing factors to weight gain, specifically fat mass gain, during the transition out of adolescence and into adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…As such, much effort has been put into childhood interventions to prevent childhood onset of OWO, which would track into subsequent ages . Children and adolescents with healthy or NW also become adults with OWO; however, there is a lack of data investigating contributing factors in the years beyond adolescence, EA, during which fat mass accrual and transition to OWO occur . The period of EA is characterized by both total body and trunk fat (TBF and TrF) gains, attributed in part to changes in lifestyle factors, such as decreasing or sustained low physical activity (PA) and negative dietary changes .…”
Section: Introductionmentioning
confidence: 99%